Is there an optimal age for total knee arthroplasty?: A systematic review - Lee, Seung Hoon (Knee Surg Relat Res, 2020)
PURPOSE: The purpose of this systematic review was to elucidate the optimal age for patients undergoing total knee arthroplasty (TKA), to optimize the balance between the benefits and risks by analyzing patient-reported outcome measurements (PROM), revision rate, and mortality according to age. MATERIALS AND METHODS: A rigorous and systematic approach was used and each of the selected studies was evaluated for methodological quality. Data were extracted according to the following: study design, patients enrolled, patient age at the time of surgery, follow-up period, PROM, revision rate, and mortality. RESULTS: Thirty-nine articles were included in the final analysis. The results were inconsistent in the PROM analysis, but there was consensus that PROM were good in patients in their 70s . In the revision rate analysis, there was consensus that the revision rate tends to increase in TKA in younger patients, but no significant difference was observed in patients > 70 years of age. In the mortality analysis, there was consensus that the mortality was not significantly different in patients < 80 years of age, but tended to increase with age. CONCLUSION: This systematic review shows that the PROM were good when TKA was performed in patients between 70 and 80 years of age; the best PROM could be achieved around 70 years of age, and no significant difference in the revision or mortality rates was observed between 70 and 80 years of age; however, mortality tended to increase with age. Therefore, the early 70s could be recommended as an optimal age to undergo TKA. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s43019-020-00080-1.